Nomogram for calculation of left ventricular volumes. - Saksena, F B (1977)
A nomogram has been devised for the rapid derivation of left ventricular volumes from single-plane angiograms obtained in the 30 degrees right anterior oblique projection. The left ventricular volumes are derived from the use of the area-length formula of Dodge. The computed left ventricular volumes may then be adjusted to correspond to the actual volumes by an appropriate conversion chart.